What Matters for the Job Performance of Field Advisors: A Case of Participatory Forest Management in Madhupur Sal Forest in Bangladesh. (28th May 2022) - Kabir, Khondokar H.; Knierim, Andrea; Chowdhury, Ataharul; Darr, Dietrich
ABSTRACT: This study analyzed the determinants of the job performance of field advisors who were working in a remote forest area. A stakeholder analysis was conducted to identify advisory organizations working in the Madhupur Sal forest, Tangail, Bangladesh. Data from 87 field advisors were collected in face-to-face interviews. Binary logistic regression analysis was performed to identify the factors affecting the performance of the field advisors. Various factors were identified at the organizational and the individual levels. Important organizational-level variables were coordinated with other organizations, existence of economic incentives for fieldwork, presence of a monitoring and evaluation system, total number of staff, staff training, presence of a system of rewards and punishments, existence of travel allowance, and access to computer and internet facilities. Variables at the individual level included the interaction with forest researchers and the use of a group approach for information sharing as significant determinants of satisfactory performance of field advisors.